Comparison of transplant outcomes from matched sibling bone marrow or peripheral blood stem cell and unrelated cord blood in patients 50 years or older. Issue 5 (28th March 2016) - Konuma, Takaaki; Tsukada, Nobuhiro; Kanda, Junya; Uchida, Naoyuki; Ohno, Yuju; Miyakoshi, Shigesaburo; Kanamori, Heiwa; Hidaka, Michihiro; Sakura, Toru; Onizuka, Makoto; Kobayashi, Naoki; Sawa, Masashi; et al.
Abstract : Older recipient and donor age were associated with higher incidences of severe graft‐versus‐host disease (GVHD) and mortality after allogeneic hematopoietic stem cell transplantation from matched sibling donors (MSDs) and matched unrelated donors. Since a lower incidence of severe GVHD is advantageous in unrelated cord blood transplantation (CBT), a higher incidence of GVHD using older MSDs could be overcome using cord blood for older patients. We retrospectively analyzed Japanese registration data of 2, 091 patients with acute myeloid leukemia, acute lymphoblastic leukemia (ALL), and myelodysplastic syndrome aged 50 years or older who underwent MSD bone marrow transplantation (BMT) ( n  = 319), MSD peripheral blood stem cell transplantation (PBSCT) ( n  = 462), or unrelated CBT ( n  = 1, 310) between 2007 and 2012. Median age of MSD was 56 (range, 38–74) years. Compared with CBT, the risk of developing extensive chronic GVHD was higher after BMT (hazard ratio [HR], 2.00; P  = 0.001) or PBSCT (HR, 2.38; P  < 0.001), and transplant‐related mortality was lower after BMT (HR, 0.61; P  < 0.001) or PBSCT (HR, 0.63; P  < 0.001). Relapse rates were not significant difference between three groups. Although overall mortality was lower after BMT (HR, 0.67; P  < 0.001) or PBSCT (HR, 0.75; P  = 0.002) compared with CBT, the rates of a composite endpoint of GVHD‐free, relapse‐free survival (GRFS) were not significant difference between three groups. These data showed that MSDs remain the best donor source for older patients, but CBT led to similar GRFS to BMT and PBSCT. Am. J. Hematol. 91:E284–E292, 2016. © 2016 Wiley Periodicals, Inc.